Effect Of Respiratory Proprioceptive Neuromuscular Facilitation In Phase One Cardiac Rehabilitation – A Randomized Controlled Trial - Naik, Varun; Vernekar, Smitha (Nepalese Heart Journal, 2024)
Patients undergoing coronary artery bypass graft (CABG) and valve replacement surgery often develop pulmonary complications in early post-operative period as results to decreased lung function and impaired cough reflex. The recent study aimed to determine and compare effectiveness of respiratory PNF to conventional physiotherapy in improving the pulmonary function and airway clearance in early period of CABG and valve replacement patients. Methods: A Randomized control trial was conducted on 46 subjects with median sternotomy incision. Participants were assigned to either Group A (n=23) received phase one of cardiac rehabilitation or Group B (n=23) received phase one of cardiac rehabilitation and respiratory Proprioceptive Neuromuscular Facilitation (PNF). The sessions were carried for 30 min for five consecutive days twice a day. outcome measure was peak flow meter, thoracic expansion measure, sputum volume, respiratory rate, heart rate and blood pressure. The outcome measures were evaluated on baseline and post 5 days of the intervention. Results: within group analysis revealed that both the interventional and control groups improved significantly on all outcome measure with p-value less (p<0.005) than in all parameters expect for blood pressure, whereas a significant difference was seen in between group analysis in blood pressure (0.0500) and hear rate (0.0210). Conclusion: the study concluded that phase one cardiac rehabilitation along with respiratory PNF are effective in improving the lung function, rate and depth of breathing, sputum clearance.